"I don't know why I'm here": from knot-working to not-knowing. Issue 2 (12th August 2014) - Wegener, Charlotte
Abstract : Purpose: – The purpose of this paper is to examine the idea of getting lost during field studies as a point of departure for reframing the initial research question. Design/methodology/approach: – The paper presents field notes and reflections to illustrate the process of tracing innovation in the field by means of a theoretical concept – "knot-working" as proposed by Engeström (2008). By paying attention to seemingly irrelevant empirical data and experiences of being lost, the author infuses another theoretical concept – "not-knowing" as proposed by Lather (2007). Findings: – By questioning research questions, it becomes possible to challenge conventional assumptions in the field under study as well as assumptions underlying existing theory. It is argued that good research questions evolve iteratively throughout a study and might be even more valuable than answers (Alvesson and Sandberg, 2013). The paper illustrates how not-knowing can serve as a methodological perspective from where ordinary held assumptions can be reconsidered, thus paving the way for novel research questions that can enhance established theory. Originality/value: – The paper questions the initial research question: "How is the elderly care sector affected by innovation imperatives, " and ends up posing the reverse question: How are innovation imperatives affected – or how could they be affected – by the notion of care.